Heating and de-icing function in conductive concrete and cement paste with the hybrid addition of carbon nanotubes and graphite products. (26th February 2021) - Farcas, C; Galao, O; Navarro, R; Zornoza, E; Baeza, F J; Del Moral, B; Pla, R; Garcés, P
Abstract: This paper aims to study the viability of conductive cement paste and conductive concrete with the hybrid addition of carbon nanotubes (CNT) and graphite powder (GP) as a self-heating material for heating, ice formation prevention and de-icing in pavements. Different heating tests, ice-preventing tests and de-icing tests were performed with cement paste and concrete specimens. Results confirm that the conductive cement composites studied, with the addition of 1% CNT + 5% GP, exhibited heating, de-icing and ice-prevention properties, when applying constant AC/DC voltages between the two end sides of each specimen, with relatively low energy consumption. The main contribution of this work is to achieve a sufficient conductivity level for the development of the heating and de-icing function using this hybrid addition in concrete, which has not been used so far, in order to be applied in real concrete structures.